Personal Hygiene Practices related to Genito-urinary Tract and Menstrual Hygiene Management in Female Adolescents - Sukhee Ahn; Kyungmi Cho (Korean Society of Women Health Nursing, 2014)
PURPOSE: The study was to survey personal hygiene practice related to genito-urinary tract and menstrual hygiene management in female adolescents in order to obtain basic information for health education. METHODS: With a descriptive survey design, 389 adolescents were recruited via convenience sampling in Korea. Survey instrument was the feminine and menstrual hygiene practice and perception of vaginal douching. Data were collected from a self-administered structured questionnaire. RESULTS: Mean age of adolescents was 16.09 and menarche was at 13.21. While washing hands after urination/defecation was highly performed, wipe front to back and wash with soap and water were reported as being not well done. Twenty-eight percent reported douching habit. More positive beliefs about douching were reported by adolescents who practiced douching. Menstrual hygiene management was very appropriate with changing sanitary pads regularly with hand washing; but less performed for limiting bathing activity during menstrual periods and washing hands after activity of genito-urinary area. CONCLUSION: Some adolescents practiced inadequate hygiene practices especially for body cleansing during menstrual period and vaginal douching. It is important to develop and implement school health education programs on feminine and personal hygiene for adolescents to help them perform adequate health behaviors.